(untitled) (The International Journal of Educational Sciences and Arts, 2022)
The problem of current study is to raise interest in studying the issue of measuring the quality of university library services, to contribute to knowing the extent of commitment of the central library at King Abdulaziz University, in applying standards and indicators for improving the performance of libraries to determine the level of performance and the accompanying shortcomings from the point of view of students and workers at the university. the mom. Accordingly, the current study consists in answering the main question: What is the reality of measuring the quality of the services of the central library at King Abdulaziz University from the perspective of workers and the beneficiary community of students, faculty members, and administrative staff, and ways of development and improvement? Accordingly, the researcher used the analytical descriptive approach due to its suitability to the subject of the study, and the study derives its importance from the results and facts it presents about the reality of digital information services in university libraries, highlighting some features of weakness, strength, and the processes used in relation to measuring the performance of the university library service under study in the light of approved standards and measures. For the researcher’s sincere desire to be a guiding path in the libraries of our university. The study ended with a list of sources and references and a set of results, recommendations and suggestions emanating from knowledge, and a diagnosis of the reality of the situation in relation to the subject of the study, with the aim of developing a better vision for the development of future performance and diagnosing shortcomings, imbalances and strengths.